2013
DOI: 10.1117/12.2026157
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity analysis for OMOG and EUV photomasks characterized by UV-NIR spectroscopic ellipsometry

Abstract: We investigated the potentials, applicability and advantages of spectroscopic ellipsometry (SE) for the characterization of high-end photomasks. The SE measurements were done in the ultraviolet-near infrared (UV-NIR) wavelength range from 300 nm to 980 nm, at angle of incidences (AOI) between 10 and 70° and with a microspot size of 45 x 10 µm² (AOI=70°). The measured and spectra were modeled using the rigorous coupled wave analysis (RCWA) to determine the structural parameters of a periodic array, i.e. the pit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In isotropic samples, the M 22 element equals one independent of the wavelength and azimuth angles [Eq. (9)]. For the investigated line gratings, this value was only conserved for azimuth angles of 0°, 90°, 180°, and 270°.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In isotropic samples, the M 22 element equals one independent of the wavelength and azimuth angles [Eq. (9)]. For the investigated line gratings, this value was only conserved for azimuth angles of 0°, 90°, 180°, and 270°.…”
Section: Resultsmentioning
confidence: 99%
“…The two different types of masks consist of different layer stacks and material dispersions, which were determined in multiple angle spectroscopic ellipsometry measurements. The complete stacks of both masks can be found in a previous publication [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that ellipsometry parameters were more sensitive to CD variations when a smaller AOI was applied. 7 The modelling was done with an extended version of the SpectraRay software. 24 The scanning electron microscope (SEM) images were taken with a LEO 1560 system.…”
Section: Methodsmentioning
confidence: 99%